Mulching materials affect growth and yield characters of cucumber (Cucumis sativus cv. Malini) under drip irrigation condition in Chitwan, Nepal - Karki, A.; Sapkota, B.; Bist, P.; Bista, K.; Dutta, J. P.; Marahatta, S.; Shrestha, B. (Journal of Agriculture and Forestry University, 2020)
An experiment was done to evaluate the effect of mulching materials on growth and yield characters of cucumber (var: Malini) under drip irrigation condition during February to May 2018 in Chitwan district, Nepal. The experiment was done by using Randomized Complete Block Design (RCBD). Accordingly, four different mulching materials, viz. silver on black polyethylene mulch, black polyethylene mulch, rice straw mulch, and rice husk mulch were used as treatments. Each treatment was replicated four times. Un-mulched plot served as control. Mulching improved growth and yield characters of cucumber. Plant height and number of leaves were significantly higher (p